Are global value chains for sale? On business-state relations in the MENA region - Nora Aboushady; Chahir Zaki (German Institute of Development and Sustainability (IDOS), 2023)
We use new data on political connections from the World Bank Enterprise Surveys to examine the impact of connections on firms' participation in global value chains (GVCs) for six MENA countries (Morocco, Tunisia, Egypt, the West Bank and Gaza, Jordan, and Lebanon). In addition to political connections, we construct several measures of "political influence" based on available data on lobbying and grand corruption. We also explore whether political connections help firms overcome barriers to trade and investment and increase their participation in GVCs at the extensive and intensive margins. Our findings suggest that political connections do matter for firms' GVC participation. The impact is more pronounced for firms that combine political connections with informal payments to influence policymaking. Our findings on the significance of trade and investment barriers for GVC participation for different categories of firms' political influence are - however - inconclusive.
Keywords: F10; F14; P00; 330; GVCs; political connections; bribes; MENA region